Advertising and Gender Issues in Nigeria: Between Ethics and Socio-Cultural Sentiments - Steven Anu’ Adesemoye; Ramson Oloche Acheme; Haruna Mohammed Salisu (Britain International for Academic Research (BIAR-Publisher), 2025)
One of the roles advertising plays in society is mirroring the sociocultural values and norms of the people; it blends the target audience’s cultural practice with the features of a product. This appeal is based on findings from sociologists that people held their culture dearly and would patronize any product which aligns with their cultural identity and norms. Modern-day Nigerian advertising scene has witnessed many advertisements which have explored our cultural norms to the pleasure of many, however, recent advertisement copies have attracted criticisms and backlash after featuring some cultural practices in the line of gender portrayal. The telecommunication advertisement of MTN titled ‘Mama na Boy’ was not only met with heavy criticism but was instantly ordered to be scrapped by the Advertising Practitioner Council of Nigeria. Following the backlash by local Women's rights activists, the advertisement became a topical and controversial issue in Nigeria. Scholars, observers, and human rights movements all debated the issue and its implications on our society. What many did not consider is if the advertisement violated our indigenous norms of gender roles and cultural practices. This study observed that public discourse largely influences ethical issues and takes precedence over professional considerations. In our contemporary society, where consumers/audiences have taken to more active role in media content, it has become an enormous task for ARCON to professionally regulate the content of advertising copies since public criticisms are often done out of sentiment. The concern of this study is asking if ARCON will be allowed to do its job without being affected by public sentiment. The public rhetorics may sound fair and ideal but they often fail to see facts as they were. The recent Olympic games in Asia have revealed that gender inequality is not a man-made issue but a biological phenomenon. A male athlete at the 2019 Olympic games who overran the female racer on the track has also sparked criticism by the general public, but this time it wasn’t an advert portrayal but a real-life scenario. This study engages in critical discourse upon this background, using the Benevolent Sexism and Perception theories as a backdrop.